Game Studies. Methodological Approaches from the History of Medieval Art: (English version) - Castiñeiras López, Javier (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2021)
This article presents an updated state of the art about the relation of videogames with the cultural sphere and the historical disciplines. Specifically, we will try to address the role that the History of Medieval Art can play in the analysis and assessment of these cultural objects from a double way defined, on one side, by the historical Middle Ages and, on the other side, by the recreated medioevo. The Assassins Creed saga and titles as Bloodborne or A Plague Tale: Innocence, offer very particular visions of medieval and neomedieval architecture, all of them likely to be part of the cannon of medievalizing works of contemporary culture and, therefore, be object of study for the History of Medieval Art.